Synthesis of White Mineral Trioxide Aggregate (WMTA) Using Silica from Rice Husk and Calcium Carbonate from Limestone - Anwar Jaman; Muhammad Ulin Nuha ABA; Oksita Asri Widyayanti (Jurnal Kimia Sains dan Aplikasi, 2023)
White Mineral Trioxide Aggregate (WMTA) was produced using silica as the initial material extracted from rice husk ash and calcium carbonate limestone. This research was initiated by calcinating rice husk ash at 700°C for 3 hours. Silica extraction was performed using 2 M NaOH and added HCl. The extract precipitate was washed using deionized water. Calcium carbonate was made from limestone using 1 M HNO3 and NH3 and continued with carbonation. WMTA was produced by mixing SiO2, CaCO3, and Al2O3. The mixture was homogenized with deionized water and heated, then pellets calcined made at a temperature of 1000°C, and calcination products were added Bi2O3. Synthesized WMTA characterized using TGA/DSC, FTIR, and XRD showed the presence of Ca3SiO5, Ca2SiO4, and Ca3Al2O6 phases, which were like ProRoot’s WMTA.